ANALISIS AKAR MASALAH PANJANGNYA WAKTU TUNGGU PROSES ADMINISTRATIF PEMULANGAN PASIEN RAWAT INAP - Sari, Dita Prawita; Harijanto, Tatong; Susilo, Harsono (STIKes Maharani Malang, 2017)
Introduction: One critical area in the overall patient care flow in the hospital is the process of patient discharge . The high number of bed usage in the treatment room posed a problem in terms of postponing admissions and transferring new patients to the treatment room. One of the causes of postponement of admission and transfer of patients is a very long process of discharge patients 3-4 hours for general patients and more than 4 hours for insurance patients. Method: The purpose of this research is to analyze the root of the problem on the length of waiting time of administrative process of discharging patient in Hospital